Shared Values and Strategic Implementation Success - Ejoh, Ejiro; Omoile, Patrick A. (International Journal of Public Administration Studies, 2023)
In this seminar work, we delve into the critical relationship between shared values and the success of strategic implementation in organizations. We explore the significance of shared values as the core beliefs and principles that unite employees and stakeholders, contributing to successful strategic implementation. Furthermore, the paper examines the impact of shared values on strategic implementation outcomes and how they help achieve organizational strategic goals. Additionally, we outline effective strategies to cultivate a shared values culture within organizations, fostering an environment where shared values thrive.